Characterization of Antibodies Induced by Human Factor VIII in a Murine Knockout Model of Hemophilia A - Reipert, Birgit M.; Ahmad, Rafi U.; Turecek, Peter L.; Schwarz, Hans P. (Thrombosis and Haemostasis, 2000)
To investigate the usefulness of factor VIII (FVIII) knockout mice as an animal model of hemophilia A, we characterized the antibody response in FVIII knockout mice to recombinant human FVIII, administered intravenously or subcutaneously with or without adjuvant, and compared results to those in normal mice. Anti-factor VIII antibodies were detected after both intravenous and subcutaneous administration, with the highest titers after subcutaneous administration plus adjuvant. Depending on the administration strategy, knockout mice formed antibodies more rapidly and developed higher titers of inhibitory antibodies (Bethesda) than normal mice, suggesting differences in epitope specificity. Blotting thrombin cleavage products separated by gel electrophoresis showed that both strains developed antibodies against the nonfunctional B domain as well as against functional domains of factor VIII. The antibodies were mainly of the IgG1 subclass and resembled type I antibodies in hemophilia A.
Keywords: Hemophilia A; animal model; knockout mice; factor VIII; antibodies